Cardiac tissue engineering: Multiple approaches and potential applications - Gisone, Ilaria; Cecchettini, Antonella; Ceccherini, Elisa; Persiani, Elisa; Morales, Maria Aurora; Vozzi, Federico (Frontiers in Bioengineering and Biotechnology, 2022)
The overall increase in cardiovascular diseases and, specifically, the ever-rising exposure to cardiotoxic compounds, has greatly increased in vivo animal testing; however, mainly due to ethical concerns related to experimental animal models, there is a strong interest in new in vitro models focused on the human heart. In recent years, human pluripotent stem cells-derived cardiomyocytes (hiPSC-CMs) emerged as reference cell systems for cardiac studies due to their biological similarity to primary CMs, the flexibility in cell culture protocols, and the capability to be amplified several times. Furthermore, the ability to be genetically reprogrammed makes patient-derived hiPSCs, a source for studies on personalized medicine. In this mini-review, the different models used for in vitro cardiac studies will be described, their pros and cons analysed to help researchers choose the best fitting model for their studies. Particular attention will be paid to hiPSC-CMs and three-dimensional (3D) systems since they can mimic the cytoarchitecture of the human heart, reproducing its morphological, biochemical, and mechanical features. The advantages of 3D in vitro heart models as compared to traditional 2D cell cultures will be discussed, and the differences between scaffold-free and scaffold-based systems will be also spotlighted.